Renewable energy systems in Southeast Asia - Green, Joanta H. (PennWell Pub. Co., 1996)
Renewable Energy Systems in Southeast Asia surveys the market prospects of nonconventional power-generating and transforming equipment in the Pacific Rim, a region where many newly industrialized and oil-producing countries are found. This one-of-a-kind book provides detailed coverage of solar photovoltaic systems, small hydropower, wind energy, solar thermal, and biomass energy alternatives. It highlights the social, political, economic, and environmental consequences of the utilization and issemination of renewable energy systems. This book is a must reading for engineers working on small power projects, private power developers, renewable energy specialists, energy policy makers, as well as renewable energy manufacturers looking ot expand their markets in the region.